Predictive tools in financial policy for profitable firms: reality or mirage? - Díaz, Luis Francisco Ramírez; Penagos, Carlos Orlando Parra (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article is addressed from the strategic perspective in finances, its goal is to show recent technical equipment related to procedures/practices of financial analysis of prediction and its use in the management, and also to understand at what point there is an optimal capital structure. Forthisreason we construct a conceptual support based on trade-off theory and the study of techniques and tools that lead to measure the results obtained in a management period. We conclude that when the authors use statistics, they establish patterns that characterize organizations and that are treated in the field of prediction and description.